The effect of marketing mix and service quality on customer satisfaction in increasing customer loyalty at New Panjang Jiwo Resort - Hawari, Milzam Satya; Krisnatuti, Diah; Asikin, Zenal (Indonesian Journal of Multidisciplinary Science, 2024)
New Panjang Jiwo Resort, located in Bogor Regency, is a popular tourist destination for both domestic and foreign tourists. Despite various marketing activities, the resort has faced negative reviews and fluctuating visitor numbers. To maintain its sustainability, the resort needs to employ a right marketing strategy and good service quality to increase customer satisfaction and loyalty. This research aims to identify customer characteristics of New Panjang Jiwo Resort, analyze the effect of the marketing mix and service quality on customer satisfaction and loyalty. The sample consisted of 155 respondents aged 26-35 years, with 60% being women. The average domicile of visitors at the resort is from Jabodetabek and works as a private employee with a lower middle income income category. The results showed that the overall variables of the marketing mix, service quality, customer satisfaction, and consumer loyalty at New Panjang Jiwo Resort are included in the high category. The marketing mix variable had the highest average value compared to other variables. SEM-PLS analysis showed that the marketing mix and service quality had a positive and significant effect on customer satisfaction and satisfaction had a positive and significant effect on loyalty. The managerial implications of this research include building road directions at every crossroads along the main road to the resort, regular maintenance of room air conditioning, and conducting training to improve the quality of work provided by employees. This will help ensure that the resort's services are more tailored to the wishes and needs of customers.